2019
DOI: 10.3390/nano9020255
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Silicon Oxide Thin Films Doped with Zinc and Copper Grown by Atmospheric Pressure Plasma Chemical Vapor Deposition

Abstract: Zn-doped and Cu-doped SiOx films were synthesized by atmospheric pressure plasma chemical vapor deposition to study their antibacterial efficiency against Gram-negative Escherichia coli and their cytotoxic effect on the growth of mouse cells. Zn-rich and Cu-rich particles with diameters up to several microns were found to be homogeneously distributed within the SiOx films. For both doping elements, bacteria are killed within the first three hours after exposure to the film surface. In contrast, mouse cells gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…The Ag appears to be effectual only at elevated temperatures [19], whereas Cu was found—using in vitro tests—to have antibacterial ability at ambient conditions [20]. For this reason, Cu is being investigated as an antibacterial element with increased frequency in thin films [21,22], ionic form [23,24], and in alloys [17,25,26]. In particular, Zhang et al [27] have investigated the addition of Cu in titanium and found that there are discrepancies in the literature regarding required copper content and the mechanisms causing bacterial reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The Ag appears to be effectual only at elevated temperatures [19], whereas Cu was found—using in vitro tests—to have antibacterial ability at ambient conditions [20]. For this reason, Cu is being investigated as an antibacterial element with increased frequency in thin films [21,22], ionic form [23,24], and in alloys [17,25,26]. In particular, Zhang et al [27] have investigated the addition of Cu in titanium and found that there are discrepancies in the literature regarding required copper content and the mechanisms causing bacterial reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, metal embedded SiOx films produced by high-temperature air plasmas are effective for antibacterial applications. For example, hexamethyldisiloxane (HMDSO) was used as a primary precursor and solutions with silver nitrate AgNO3, zinc nitrate Zn(NO3)2 and copper nitrate Cu(NO3)2, in a 1:1 volume mixture of isopropanol and water, were sprayed into the plasma as secondary precursors (Zimmermann, et al, 2011;Jager, et al, 2019). After separation from the precursor molecules, Ag, Zn and Cu elements bind to oxygen, thus forming metal oxides that are subsequently incorporated into the SiOx film.…”
Section: Depositionmentioning
confidence: 99%
“…In many studies, titanium implants are coated with sol-gel films containing metal additives, such as Ag [98][99][100], Cu [101], or Zn [102]. Fu et al [103] and Massa et al [104] reported the impact of Ag on bacteria growth and the biofilm formation.…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%